2016
DOI: 10.1159/000450749
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Changes May Precede Gray Matter Loss in Elderly with Subjective Memory Impairment

Abstract: Background/Aims: A limited number of studies addressed MRI-based neurodegenerative changes in subjective memory impairment (SMI). We investigated changes in white matter (WM) microstructures as well as gray matter (GM) macrostructures in subjects with SMI of high and low risk for progression. Methods: A modeling scale (score range, 0-6) developed for prediction of SMI progression was used to divide SMI subjects (n = 46) into two groups: a high risk of progression (score ≥3; n = 19) and a low risk of progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Another investigation categorized individuals with SCD into a high-risk group and a low-risk group based on age, ApoE genotype, K-MMSE recall score and the Seoul Verbal Learning Test. The high-risk group showed more severe microstructural disruptions with reduced FA in the tracts connecting the hippocampus, parahippocampal gyrus, supramarginal gyrus and parts of the frontotemporal lobes [ 118 ].…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…Another investigation categorized individuals with SCD into a high-risk group and a low-risk group based on age, ApoE genotype, K-MMSE recall score and the Seoul Verbal Learning Test. The high-risk group showed more severe microstructural disruptions with reduced FA in the tracts connecting the hippocampus, parahippocampal gyrus, supramarginal gyrus and parts of the frontotemporal lobes [ 118 ].…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
“…Research combining MRI volumetric and DTI measures suggested that individuals with SCD showed a lower entorhinal cortical volume, lower FA and higher MD in the hippocampal body and entorhinal WM [ 78 ]. According to another study [ 118 ], individuals with SCD with a high risk of progression had more severe WM disruption than the low-risk SCD group but no evident gray matter atrophy. Thus, relatively high-risk SCD may predict an underlying microstructural disruption in the WM that precedes gray matter atrophy during AD progression.…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…These changes include reduced integrity in white matter tracts connected to the medial temporal lobe (MTL) [ 2 , 31 ], the cingulum and in the tracts of the temporo-parietal regions such as the superior longitudinal fasciculus [ 1 , 7 ]. These changes in white matter structure have been directly associated with Wallerian degeneration independent of cortical atrophy [ 3 , 7 , 28 ]. Moreover, AD cases with severe cortical AD pathology and severe WML exhibited only minimal SVD pathology at post-mortem examination [ 17 , 40 ], indicating that SVD was not the primary cause of WML in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…SCD cases have a two-fold increased risk to develop dementia and a six-fold increased risk to develop MCI over on average four years of clinical follow-up compared with cognitively normal people without subjective cognitive complaints [11]. Several studies found significant differences in DTI parameters, such as fractional anisotropy or mean diffusivity, in SCD cases compared with controls [12][13][14][15]. Studies on the diagnostic utility of DTI markers, however, for the discrimination between SCD cases and controls are still scarce.…”
Section: Introductionmentioning
confidence: 99%